Integrating Zero-Waste Management into Corporate Governance: An Application of the MER Model of Integral Management and Governance - Čufar, Matic; Belak, Jernej (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This paper examines how the MER model of integral management and governance (MER model) can be applied to assess the integration of zero-waste management into corporate governance. It evaluates whether waste reduction is addressed merely as an operational activity or embedded across political, strategic, and operational levels of management. Methodology: The study adopts a qualitative multiple case design based on content analysis of annual reports of selected companies. Waste-related disclosures (pursuant to ESRS requirements) were evaluated using the MER model to assess governance-level integration and cross-level coherence. Findings: The results indicate that companies predominantly address waste management at the operational level, while strategic integration and embedding at the political level remain limited. Value: The study demonstrates how the MER model can be applied to analyse zero-waste management as a governance issue rather than solely as a technical or environmental practice.